Poor diet in fruits and risk of colorectal cancer: Dieta deficiente en frutas y riesgo de cáncer colorrectal - Contreras-Tataje, Jorge Segundo (2023)
Sr. Editor After reading the article by Lobato-Jeri, C et al. which is entitled "Clinical surgical characteristics of patients aged 75 years or older colostomized in the national hospital Edgardo Rebagliati Martins with DOI: 10.25176/RFMH.v16.n2.667, published in 2016, in your prestigious journal of Facultad de medicina humana de la Universidad Ricardo Palma, I must say that it has been a pleasure to have studied it, because it deals with a very relevant topic for the public health of our country. This study covers the characteristics that exist in elderly patients who underwent colostomy surgery. What caught my attention was that, of the patients analyzed in their publication, a large percentage (42.11%) had unresectable colorectal cancer that caused intestinal obstruction, which led them to have a colostomy.